1991
DOI: 10.7901/2169-3358-1991-1-167
|View full text |Cite
|
Sign up to set email alerts
|

Natural Cleaning of Shorelines Following the Exxon Valdez Spill

Abstract: Field observations have identified a number of natural processes that contributed to the cleanup of the Exxon Valdez spill. This paper focuses on physical processes that remove oil residue from shoreline sediments. Data from shoreline surveys at 16 monitoring sites in Prince William Sound show significant reductions in both surface oil coverage and sediment oil content during the period from September 1989 to March 1990, while cleanup activities were suspended. Natural cleaning appeared to be do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The authors conclude that the elevated mineral potentials and increased bacterial numbers showed that degradation was enhanced even though they did not carry out direct chemical analyses. In contrast, other observers working in the Prince William Sound area, and around the same time, concluded that 'natural cleaning appeared to be dominated by wave action during storms' (Jahns et al 1991). It has also been claimed that surfactants formed by Pseudornonas aeruginosa were effective in cleaning gravel beaches following the 'Exxon Valdez' spill (Harvey et al 1990).…”
Section: Results To Datementioning
confidence: 99%
“…The authors conclude that the elevated mineral potentials and increased bacterial numbers showed that degradation was enhanced even though they did not carry out direct chemical analyses. In contrast, other observers working in the Prince William Sound area, and around the same time, concluded that 'natural cleaning appeared to be dominated by wave action during storms' (Jahns et al 1991). It has also been claimed that surfactants formed by Pseudornonas aeruginosa were effective in cleaning gravel beaches following the 'Exxon Valdez' spill (Harvey et al 1990).…”
Section: Results To Datementioning
confidence: 99%
“…• Clay-oil flocculation-this process reduces adherence of oil to shore substrates and facilitates natural cleaning, as has been described for Prince William Sound after the Exxon Valdez spill [20];…”
Section: Processes and Timescales For Natural Cleaningmentioning
confidence: 99%
“…Oil traveled as far as 750 km from the spill site, contacting 1750 km of shoreline along the way (900 km in PWS) (76,100). Some beached oil was collected by cleanup crews, but much eventually ended up back in the water column, lifted off beaches when they were washed by humans or pummeled by winter waves (67,82,107,172).…”
Section: Evos Oil Trajectorymentioning
confidence: 99%